ANALISIS KEPUASAN PELANGGAN INTERNAL DAN EKSTERNAL SEBAGAI DASAR PENYUSUNAN QUALITY FRAMEWORK PELAYANAN KESEHATAN DASAR DI PUSKESMAS KABUPATEN BANYUWANGI - , As'adul Anam; , dr. Tjahjono Kuntjoro, MPH, DrPH. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Complaints against the services at health centers often heard directly or through the mass media. Target complaint is the attitude or actions of both doctors and paramedics are less quick to respond. So that the patient requires a long waiting time for consultation, administrative services convoluted cause delays in health services, drug supplies is minimal, less availability of medical facilities and others. The low quality of service due to the gap between perceptions and expectations of customers, therefore PHC in Banyuwangi needs to analyze the external and internal customer satisfaction, in order to design a quality framework of primary health care clinics in Banyuwangi. Objective: To know the expectations and perceptions of internal and external customers for the quality of care in health centers, knowing the gap between expectations and perceptions of customers as an ingredient in developing a strategy of development of quality services in health centers. Methods: Descriptive case study. Location of research in health centers Wongsorejo and health centers Bajulmati Wongsorejo Banyuwangi. Samples are 100 patients and 16 health workers. How sampling purposive sampling with inclusion criteria. To develop quality framework for observations of the element of local government, health agencies, professional organizations and societies. Results: The results of this study show that the gap between perceptions and expectations of internal and external customers on quality of care. The highest gap score on each dimension of quality is a priority for improved quality and an advanced basis for the preparation of this quality framework. Items that are prioritized by external customers include: an explanation of service procedures, service schedules on time, patients do not wait too long, the officer being friendly, fair service and cleanliness inspection equipment. While the items are prioritized by the internal customers, among others, pay attention to problems that might occur, responsive to the needs of co-workers, skilled workers, a commitment between workers and customers, fellow co-workers give each other personal attention and performant workers neat. Conclusion: A strategy for the development of quality of service based on external and internal customer satisfaction among others include education and training of officers, perform services in accordance with the SOP, complete service support equipment, carry out marketing activities and establish quality control.